THE SCIENTIFIC LANGUAGE OF AUGUSTO DOS ANJOS - Aragão, Maria do Socorro Silva de (2020)
Considering the theoretical aspects of Terminology, a science that studies termsor “technical and scientific concepts” (BARROS, 2004: 57), this article analyzes thelanguage of Augusto dos Anjos, which presents a wealth of scientific and philosophicalterms, surprising use in a poetic language.